Composite oil field acidification corrosion inhibitor and preparation method thereof

CN122917754APending Publication Date: 2026-10-16BINZHOU GUANGYOU CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611208769.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]针对现有技术中油田酸化缓蚀剂高温缓蚀效力弱、酸液中易析出沉淀、储存稳定性与配伍性不足的问题,本发明提供了一种复合型油田酸化缓蚀剂及其制备方法

Benefits of technology

[0033] This invention constructs a dual Mannich base main agent molecule containing a conjugated thiadiazole heterocycle, which, in conjunction with a polyoxyethylene ether-modified alkynol, allyl thiourea, and an alternating adsorption system of iodide ion-cationic surfactant, forms a highly binding and extensive organic adsorption layer on the metal surface. The molecular structure with multiple adsorption sites enhances the coordination strength between the main agent and the metal matrix, preventing molecular desorption and chain coiling under high temperature and high concentration acid conditions. The dense organic layer can block the penetration of corrosive media such as hydrogen sulfide, significantly reducing the risk of local pitting corrosion. This effectively solves the shortcomings of traditional single Mannich base corrosion inhibitors, such as insufficient high-temperature corrosion inhibition efficiency and weak pitting corrosion control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917754A_ABST
    Figure CN122917754A_ABST
Patent Text Reader

Abstract

The application discloses a composite oil field acidification corrosion inhibitor and a preparation method thereof, and relates to the field of oil field acidification corrosion inhibitors. According to mass parts, raw material components are as follows: thiazole modified double Mannich base 25-35 parts, cerium-cysteine chelate 3-6 parts, propargyl alcohol polyoxyethylene ether 2-5 parts, ternary dispersion stabilizer 20-30 parts, and synergistic adsorption auxiliary agent 3-6 parts, and the rest is deionized water. The ternary dispersion stabilizer is compounded by ethylene glycol monobutyl ether, isopropyl alcohol and sorbitan monooleate, and the synergistic adsorption auxiliary agent is compounded by N-allyl thiourea, potassium iodide and cetyltrimethylammonium bromide. During preparation, the deionized water and the ternary dispersion stabilizer are firstly added into a reaction kettle. The corrosion inhibitor can form a combined stable organic-inorganic double-layer protective film under a high-temperature and high-concentration acid liquid environment, has a low uniform corrosion rate, has a strong local pitting corrosion prevention and control capability, and can adapt to the acidification operation requirements of high-sulfur deep oil and gas reservoirs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of compound microbial water-soluble fertilizer preparation technology, and in particular to a compound oilfield acidification corrosion inhibitor and its preparation method. Background Technology

[0002] Acidizing is a core process for reservoir stimulation and production enhancement. By injecting high-concentration acid into the reservoir to dissolve blockages in the rock pores and clear oil and gas seepage channels, it can effectively increase the productivity of a single well. However, the high-concentration hydrochloric acid, terrine acid, or thickened acid injected during the operation can cause severe electrochemical corrosion to the downhole casing and tubing, leading to safety risks such as pipe wall thinning, localized perforation, and tubing string breakage. In severe cases, it can even cause permanent abandonment of the well. Therefore, acidizing corrosion inhibitors are essential additives that must be added during acidizing operations, and their performance directly determines the safety of the operation and the effectiveness of reservoir stimulation.

[0003] As domestic oil and gas exploration and development gradually extends to deep, ultra-deep, and high-sulfur gas reservoirs, the operating conditions for acidizing operations are becoming increasingly demanding. The operating temperature in some ultra-deep wells can reach over 150°C, and the acid mass fraction used can reach up to 28%. At the same time, winter field operations require corrosion inhibitors to have low freezing points. The combined use of multiple additives requires corrosion inhibitors to have excellent compatibility with conventional well fluids such as iron ion stabilizers, clay anti-swelling agents, and drainage aids. Low-damage reservoir stimulation requires corrosion inhibitors to be free of insoluble impurities and not to clog reservoir pores. As a result, the industry's demand for high-performance composite acidizing corrosion inhibitors that are suitable for multiple scenarios continues to increase.

[0004] Currently, acid corrosion inhibitors used in field applications mainly fall into two mainstream technical categories. The first category is single Mannich base corrosion inhibitors, which are prepared through the Mannich reaction to produce organic base molecules containing amine or aromatic ring structures. These molecules rely on the lone pairs of electrons from heteroatoms in the molecule to form a coordination adsorption film on the metal surface, preventing the corrosive medium from contacting the metal substrate. This type of corrosion inhibitor has lower raw material costs and better corrosion inhibition performance under medium-low temperature and medium-low acid concentration conditions, making it the most widely used type of corrosion inhibitor in field applications. However, traditional single Mannich base molecules have a limited number of adsorption sites, resulting in a limited single-molecule adsorption coverage area. When the temperature exceeds 120°C, the molecules are prone to desorption from the metal surface. In high-concentration acid solutions, long alkyl chains are prone to molecular coiling, causing the corrosion inhibition efficiency to decrease rapidly with increasing temperature. At the same time, the adsorption film formed by a single organic molecule has inherent micropores, which can easily lead to localized pitting corrosion, failing to meet the protection requirements of high-temperature and high-acid conditions.

[0005] The second type is organic-inorganic compound corrosion inhibitors, which are compounded with metal compounds such as copper salts and rare earth salts on the basis of organic corrosion inhibitors. They rely on the deposition of metal ions in the local high pH environment of the metal corrosion cathode area to form an inorganic protective film, which complements the organic adsorption film. This can improve the corrosion inhibition performance at high temperatures to a certain extent and reduce the amount of organic main agent added. However, directly added metal salts, especially rare earth salts, have poor stability in high-concentration acid solutions and are prone to hydrolysis to form insoluble hydroxide precipitates. This not only leads to discontinuities in the inorganic deposition film and large batch-to-batch fluctuations in corrosion inhibition effects, but also clogs reservoir pores, causing permanent reservoir damage. These corrosion inhibitors often use single alcohols as solvents, resulting in products with high freezing points. Under low-temperature conditions, they are prone to component precipitation, solidification, and pipe blockage. When compounded with other well-entry additives, they are prone to charge neutralization, causing turbidity and precipitation, indicating insufficient compatibility. Some products improve high-temperature performance by compounding with small-molecule alkynyl alcohols, but small-molecule alkynyl alcohols are highly volatile and pose high occupational health risks. They are prone to rapid volatilization and failure at high temperatures and cannot fill the micropores of the corrosion inhibition film. Under high sulfur content conditions, the film layer is easily penetrated by hydrogen sulfide, resulting in insufficient pitting corrosion control.

[0006] Existing corrosion inhibitor products cannot simultaneously achieve corrosion inhibition efficiency, low reservoir damage characteristics, extreme temperature storage stability, compatibility with multiple additives, and adaptability to high sulfur content conditions under high temperature and high acid environments. They cannot meet the comprehensive protection requirements of acidizing operations in deep and ultra-deep oil and gas reservoirs. There is an urgent need to carry out targeted technical research and development to balance various performance indicators and ensure the safe and efficient conduct of acidizing operations. Summary of the Invention

[0007] To address the problems of weak high-temperature corrosion inhibition efficacy, easy precipitation in acid solutions, and insufficient storage stability and compatibility of existing oilfield acidizing corrosion inhibitors, this invention provides a composite oilfield acidizing corrosion inhibitor and its preparation method.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: a composite oilfield acidizing corrosion inhibitor, wherein the raw material composition by mass percentage per 100 parts of total mass is: 20-35 parts of thiadiazole modified bis-Mannich base, 3-8 parts of cerium-cysteine ​​chelate, 2-6 parts of propargyl alcohol polyoxyethylene ether, 1-4 parts of hexadecyltrimethylammonium bromide, 10-20 parts of dispersant stabilizer, and the balance being deionized water with a resistivity of not less than 15 MΩ·cm;

[0009] The corrosion inhibitor is suitable for oilfield acidizing operations in hydrochloric acid, terrine, and thickened acid systems with a mass fraction of 15%~28%, and provides corrosion protection for commonly used casing steels such as N80, P110, and TP125. The thiadiazole-modified bis-Mannich base uses 2,5-dimercapto-1,3,4-thiadiazole (purity not less than 99%), paraformaldehyde (formaldehyde content not less than 95%), and di-n-butylamine (purity not less than 99%) as reactants, added in a molar ratio of 1:2.1~2.3:2.0~2.2, with anhydrous ethanol (2~3 times the total mass of reactants) added as a reaction solvent. The reaction is carried out throughout the entire process. Dry nitrogen gas was used to isolate the mercapto group from air and prevent oxidation. The temperature was raised to 75-80℃ under stirring and refluxed at a constant temperature. Thin-layer chromatography was used to monitor the reaction process, with a 3:1 volume ratio of petroleum ether to ethyl acetate as the developing solvent. After the color spots of the 2,5-dimercapto-1,3,4-thiadiazole raw material completely disappeared, the temperature was maintained for another 30 minutes. Then, the solvent and low-boiling-point byproducts were removed by vacuum distillation at -0.095 MPa and 85℃ until no fraction flowed out, yielding a thiadiazole-modified bis-Mannich base product with a purity of not less than 95%, which can be used directly without additional recrystallization.

[0010] The cerium-cysteine ​​chelate is prepared using analytical grade cerium chloride heptahydrate and biochemical grade L-cysteine ​​with a purity of not less than 99% as the reaction raw material. The raw material is dissolved in deionized water at a molar ratio of 1:2.8~3.2. The reaction is carried out in the dark to prevent photolysis of cysteine. A 10% sodium hydroxide solution is slowly added at a dropping rate of 1 mL / min to adjust the pH of the system to 5.5~6.0. The system temperature is controlled at 38~42℃ under magnetic stirring at 250 r / min for a constant temperature chelation reaction of 1.5~2.5 h. During the reaction, local pH increases are avoided to prevent the formation of cerium hydroxide precipitate, resulting in a stable aqueous solution of the cerium-cysteine ​​chelate, which can be added directly or after purification.

[0011] Furthermore, based on a total mass of 100 parts, the optimal mass composition of each raw material is as follows: 28 parts of thiadiazole-modified bis-Mannich base, 5 parts of cerium-cysteine ​​chelate, 4 parts of propargyl alcohol polyoxyethylene ether, 2.5 parts of hexadecyltrimethylammonium bromide, 15 parts of dispersant stabilizer, and deionized water to make up to a total mass of 100 parts. This ratio is optimized for reservoir acidification conditions of 90~150℃, and the synergistic effect of each component reaches the optimal balance when added at a mass fraction of 1% in a 20% hydrochloric acid system.

[0012] Furthermore, the propargyl alcohol polyoxyethylene ether is a nonionic surfactant obtained by addition polymerization of propargyl alcohol with ethylene oxide under potassium hydroxide catalysis. The amount of unreacted propargyl alcohol residue in the product is not higher than 0.5%, thus avoiding the volatilization and failure of small molecule propargyl alcohol at high temperature.

[0013] The degree of polymerization of the oxyethylene structural unit of the propargyl alcohol polyoxyethylene ether is 4~6, the kinematic viscosity measured by Ubbelohde viscometer at 25℃ is 15~25mm² / s, and the cloud point measured in 1% aqueous solution according to the method specified in GB / T 5559-2010 is 45~55℃.

[0014] When the degree of polymerization is below 4, the product has poor water solubility and is difficult to disperse uniformly in water-based acid solutions. When the degree of polymerization is above 6, the adsorption activity of the alkynyl group decreases, resulting in insufficient corrosion inhibition and enhancement effects. Within this parameter range, propargyl alcohol polyoxyethylene ether can form an interleaved adsorption film layer with other corrosion inhibitors on the metal surface, filling the pores formed by the adsorption of large-sized molecules.

[0015] Furthermore, after the cerium-cysteine ​​chelate is prepared, a solid chelate can be obtained by purification and added. The specific purification process is as follows: after the chelation reaction is completed, anhydrous ethanol three times the volume of the reaction solution is added to the reaction solution under slow stirring at 100 r / min. After the addition is completed, the mixture is allowed to stand and age for 2 hours to allow the solid chelate to fully separate out. Then, the mixture is filtered. During the filtration process, the filter cake is washed three times with anhydrous ethanol. The volume of anhydrous ethanol used for each wash is twice the volume of the filter cake to wash away the unreacted free cysteine ​​and cerium chloride entrained in the filter cake.

[0016] The washed filter cake was placed in a vacuum drying oven and dried at a vacuum of -0.09 MPa and 40°C. During the drying process, the material was stirred every 1 hour to avoid local overheating and decomposition of the chelate. The chelation rate of the obtained solid cerium-cysteine ​​chelate was determined by EDTA complexometric titration to ensure that the chelation rate was not less than 92%. If the chelation rate did not meet the standard, the chelation reaction time was extended by 20 minutes until the target was met.

[0017] Furthermore, the dispersant stabilizer is composed of ethylene glycol monobutyl ether, isopropanol and Span 80, wherein the ethylene glycol monobutyl ether has a purity of not less than 99% and a boiling range of 168~172℃, the isopropanol has a purity of not less than 99.7% and a water content of not more than 0.3%, and the Span 80 has a hydroxyl value of 190~210mgKOH / g and a saponification value of 140~160mgKOH / g;

[0018] When compounding, the mass ratio of ethylene glycol monobutyl ether to isopropanol is 1:1.8~2.2, and the amount of Span80 added accounts for 2%~4% of the total mass of the dispersion stabilizer. The compounding process is as follows: first, ethylene glycol monobutyl ether and isopropanol are mixed evenly in proportion, then the weighed Span80 is added under stirring at 200 r / min, the temperature is raised to 35℃ and stirred for 15 min until Span80 is completely dissolved, and then naturally cooled to room temperature to obtain a uniform dispersion stabilizer.

[0019] This compound dispersant and stabilizer can simultaneously improve the dispersion stability of each oil-soluble corrosion inhibitor in water-based acid solutions, reduce the overall freezing point of the corrosion inhibitor, and improve the wettability of metal surfaces. If the ratio of ethylene glycol monobutyl ether to isopropanol exceeds the range, the main agent will precipitate at low temperatures. If the amount of Span80 added exceeds the range, the foaming rate of the acid solution will increase, affecting the pumping efficiency.

[0020] Furthermore, 1 to 3 parts of N-allyl thiourea are added to the raw material composition. The N-allyl thiourea has a purity of not less than 98%, is a white crystalline powder, has a melting point of 72 to 74°C, an ash content of not more than 0.1%, and does not contain free inorganic sulfur ion impurities, so as to avoid sulfur ions reacting with iron ions in the acid to form ferrous sulfide precipitates that block the reservoir pores.

[0021] The allyl group in the N-allyl thiourea molecule can undergo in-situ polymerization at the metal corrosion potential to form a continuous polymer protective film. This film complements the coordination adsorption film formed by the thiadiazole-modified bis-Mannich base and the cerium-cysteine ​​chelate, making it particularly suitable for acidification operations in highly acidic gas fields containing hydrogen sulfide. It can resist the penetration and damage of the corrosion inhibitor film by hydrogen sulfide. When the amount of N-allyl thiourea added is less than 1 part, the adaptability to high sulfur content conditions is not sufficiently improved. When it is more than 3 parts, the low-temperature dispersion stability of the corrosion inhibitor in acidic solutions will decrease, and crystallization will occur.

[0022] Furthermore, 0.5 to 2 parts of potassium iodide are added to the raw material composition, and the mass ratio of potassium iodide to hexadecyltrimethylammonium bromide is controlled at 1:1 to 1.5; the potassium iodide is an analytical grade reagent with a drying loss of no more than 1% and an iodate impurity content of no more than 0.002%, to avoid oxidizing impurities from damaging the molecular structure of the corrosion inhibitor; the iodide ions generated by the ionization of potassium iodide can preferentially adsorb onto high-energy active sites on the metal surface, reduce the free energy of the metal surface, form a negatively charged adsorption substrate, and enhance the adsorption strength of cationic thiadiazole modified bis-Mannich base, cerium-cysteine ​​chelate, and hexadecyltrimethylammonium bromide;

[0023] Within this mass ratio range, potassium iodide and cetyltrimethylammonium bromide can form an ordered adsorption layer with alternating anions and cations on the metal surface, eliminating the pores in the film caused by the repulsion of like charges by cationic surfactants, and significantly improving the stability of the corrosion-inhibiting film under high-temperature conditions of 150°C. This is suitable for the high-temperature acidizing operations in deep and ultra-deep wells. If the ratio exceeds the range, it will lead to an imbalance of charge in the adsorption layer and a significant decrease in the compactness of the film.

[0024] Furthermore, the molecular structure of the thiadiazole-modified bisMannich base includes a planar conjugated 1,3,4-thiadiazole heterocycle, two tertiary amine Mannich structural units, and two thioether bonds, with an overall molecular weight of 432. The 1,3,4-thiadiazole heterocycle can be parallelly adsorbed on the carbon steel surface, providing a large basic adsorption coverage area. The sulfur atom of the thioether bond and the nitrogen atom of the tertiary amine structure both contain lone pairs of electrons, which can form stable coordinate bonds with the empty 3d orbitals of the iron atom, achieving strong adsorption at multiple sites. The two Mannich branches extend towards the acid solution to form a hydrophobic spatial barrier, preventing the diffusion of corrosive media such as hydrogen ions and chloride ions to the metal surface.

[0025] This molecule does not contain excessively long hydrophobic alkyl chains and will not undergo molecular curling failure in high-concentration acid solutions. Its single-molecule adsorption coverage area is more than 1.8 times that of traditional acetophenone-formaldehyde-diethylamine type mono-Mannich bases, enabling the achievement of high-coverage corrosion inhibitor films with relatively low dosage.

[0026] Furthermore, the finished corrosion inhibitor is a homogeneous, transparent, reddish-brown liquid. Its freezing point, determined according to GB / T 510-1983, is below -15℃, meeting the storage and pumping requirements for winter field operations in oilfields and preventing solidification and clogging of pipelines at low temperatures. Corrosion inhibitor samples were placed in a -20℃ low-temperature constant temperature bath and a 60℃ constant temperature oven, respectively, and sealed for 72 hours. After being removed and restored to room temperature, the samples showed no stratification, crystallization, or precipitation. The transmittance measured at 600nm wavelength using a spectrophotometer deviated by no more than 2% compared to the newly prepared sample, demonstrating that the corrosion inhibitor exhibits good performance stability without component decomposition or aggregation during extreme temperature storage.

[0027] The corrosion inhibitor, when mixed with commonly used oilfield complexing iron ion stabilizers, polycationic clay anti-swelling agents, and fluorocarbon drainage aids, showed no turbidity, precipitation, or floating oil formation after standing for 2 hours in a 90°C, 20% hydrochloric acid system. Its compatibility meets the requirements of the well fluid and it will not react with other operational aids to generate precipitation that blocks reservoir pores.

[0028] Furthermore, a method for preparing a composite oilfield acidizing corrosion inhibitor, employing a polytetrafluoroethylene (PTFE) impeller for mechanical stirring throughout the process to prevent the metal impeller from being corroded by acidic components and introducing impurities, specifically includes the following steps:

[0029] S1. Weigh the thiadiazole-modified bis-Mannich base according to the formula amount and add it to half of the formula amount of deionized water. Control the stirring speed at 300 r / min and heat the system to 40~45℃ using a water bath at a heating rate of 2℃ / min. Stir at a constant temperature for 15 min. Observe the dissolution state of the system every 5 min during the stirring process. When there are no obvious oily droplets or insoluble clumps in the system, it is determined that the thiadiazole-modified bis-Mannich base is completely dissolved. During the heating process, avoid heating too quickly to prevent local temperature from becoming too high and causing decomposition of Mannich base molecules.

[0030] S2. Maintain a stirring speed of 300 r / min and a constant system temperature of 40~45℃. Add the raw materials to the system in the following order: cerium-cysteine ​​chelate, propargyl alcohol polyoxyethylene ether, and hexadecyltrimethylammonium bromide. Stir at a constant temperature for 10 min after each addition. During the stirring process, scrape off any adhering material on the stirring paddle and the inner wall of the container in time to ensure that all materials are evenly dispersed. Add the next component only after the current component has completely dissolved and the system is uniform and transparent. Avoid adding multiple components at the same time to prevent local complexing and agglomeration problems.

[0031] S3. Keep the stirring rate constant and slowly add the prescribed amount of dispersant and stabilizer to the system over a 5-minute feeding period to avoid excessively high local solvent concentrations that could cause the main agent to precipitate. After adding the dispersant and stabilizer, continue stirring for 20 minutes. Then add the remaining deionized water to adjust the total mass of the system to the prescribed amount. Continue stirring at a constant temperature for 30 minutes, controlling the system temperature to not exceed 45°C during stirring. Stop stirring when the system is a uniform, transparent, reddish-brown liquid with no visible insoluble matter. Allow it to cool naturally to room temperature and then filter it through a 100-mesh nylon filter to remove solid impurities. The finished composite oilfield acidizing corrosion inhibitor can be sealed and stored in a cool, dry place.

[0032] The present invention has the following beneficial effects:

[0033] This invention constructs a dual Mannich base main agent molecule containing a conjugated thiadiazole heterocycle, which, in conjunction with a polyoxyethylene ether-modified alkynol, allyl thiourea, and an alternating adsorption system of iodide ion-cationic surfactant, forms a highly binding and extensive organic adsorption layer on the metal surface. The molecular structure with multiple adsorption sites enhances the coordination strength between the main agent and the metal matrix, preventing molecular desorption and chain coiling under high temperature and high concentration acid conditions. The dense organic layer can block the penetration of corrosive media such as hydrogen sulfide, significantly reducing the risk of local pitting corrosion. This effectively solves the shortcomings of traditional single Mannich base corrosion inhibitors, such as insufficient high-temperature corrosion inhibition efficiency and weak pitting corrosion control.

[0034] This invention uses cysteine-chelated modified trivalent cerium as a cathode deposition type corrosion inhibitor. Through the amino acid coordinating atoms forming a stable chelate ring structure with cerium ions, the rare earth component maintains a stable dispersion state in high-concentration acid solutions. This not only retains the characteristics of rare earth components in depositing films in the metal corrosion cathode region, but also effectively fills the micropores of the organic adsorption layer, forming an organic-inorganic synergistic double-layer protective structure. Furthermore, it avoids the problem of free rare earth ions hydrolyzing to form insoluble hydroxide precipitates, significantly reducing the risk of reservoir blockage after the addition of corrosion inhibitors. This effectively solves the defects of traditional organic-inorganic compound corrosion inhibitors, such as easy precipitation, discontinuous film formation, and significant reservoir damage.

[0035] This invention employs a ternary dispersion stabilization system composed of diol ethers, low-carbon alcohols, and nonionic surfactants. Combined with a stepwise temperature-controlled addition preparation process, it improves the dispersion uniformity of each component in the water-based system, lowers the overall freezing point of the product, and enhances the storage stability of the product under extreme high and low temperature environments. At the same time, it uses high molecular weight polyether-modified alkynyl alcohols to replace easily volatile small molecule alkynyl alcohols, reducing the product's volatility and occupational health risks. The product has good compatibility with various conventional acidizing wellbore additives, and no turbidity or precipitation occurs after compounding. It does not affect the effectiveness of other additives, effectively solving the problems of traditional corrosion inhibitors such as easy solidification at low temperatures, poor storage stability, and insufficient compatibility.

[0036] This corrosion inhibitor can be adapted to the acidizing operations of oil and gas reservoirs at different depths and with different sulfur content levels. It can meet the field operation requirements in different climate zones without the need to add additional co-solvents or pour point depressants. The production process can be flexibly adjusted according to capacity and cost requirements, and it has good industrial promotion value. Attached Figure Description

[0037] Figure 1 This is an overall flow chart of the composite oilfield acidizing corrosion inhibitor proposed in this invention;

[0038] Figure 2 This is a grouped bar chart comparing the static corrosion rates at different temperatures in this invention;

[0039] Figure 3 This is a bar chart showing the comparison of storage stability and compatibility performance in this invention.

[0040] Figure 4 Radar chart showing the combined performance of the optimal formulation in this invention and traditional corrosion inhibitors;

[0041] Figure 5 This is a multi-line graph showing the temperature-corrosion rate variation trend in this invention. Detailed Implementation

[0042] The following will refer to the appendices in the embodiments of the present invention. Figure 1-5The technical solutions in the embodiments of the present invention are clearly and completely described herein. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0043] Example 1

[0044] Raw material preparation: Based on a total mass of 100g, weigh out 20g of thiadiazole modified bis-Mannich base, 3g of cerium-cysteine ​​chelate, 2g of propargyl alcohol polyoxyethylene ether, 1g of hexadecyltrimethylammonium bromide, 10g of dispersant stabilizer, 1g of N-allyl thiourea, 0.67g of potassium iodide, and the balance is deionized water with a resistivity of 15MΩ·cm.

[0045] The selected propargyl alcohol polyoxyethylene ether has a degree of polymerization of 4 in its ethylene oxide structural unit, a kinematic viscosity of 15 mm² / s at 25°C, a cloud point of 45°C, and an unreacted propargyl alcohol residue of 0.42%. The mass ratio of potassium iodide to hexadecyltrimethylammonium bromide is 1:1.5, which meets the requirements for the ratio of synergistic adsorption of anions and cations.

[0046] In the preparation of thiadiazole-modified bis-Mannich base, 2,5-dimercapto-1,3,4-thiadiazole with a purity of over 99%, paraformaldehyde with a formaldehyde content of over 95%, and di-n-butylamine with a purity of over 99% were weighed out according to a molar ratio of 1:2.1:2.0. Anhydrous ethanol, which was twice the total mass of the reactants, was added as the reaction solvent. Dry, high-purity nitrogen was purged throughout the reaction to purge air and prevent deactivation of the thiol groups. The mixture was heated to 75°C under stirring and kept at a constant temperature. The reaction was carried out under warm reflux, and the process was monitored by thin-layer chromatography. A mixed solvent of petroleum ether and ethyl acetate in a volume ratio of 3:1 was used as the developing solvent. After the colored spots of the raw material 2,5-dimercapto-1,3,4-thiadiazole completely disappeared, the temperature was maintained for another 30 min. The solvent and low-boiling-point byproducts were removed by vacuum distillation at -0.095 MPa and 85 °C until no fraction was effluent, yielding a thiadiazole-modified bis-Mannich base product with a purity of 95.3%.

[0047] During the reaction, paraformaldehyde gradually depolymerizes into free formaldehyde under reflux conditions. It first reacts with di-n-butylamine to form a semiamine aldehyde reactive intermediate, and then undergoes a nucleophilic addition reaction with two thiazole groups on the thiadiazole core, covalently grafting two Mannich side chains containing tertiary amines. Finally, a bis-Mannich base structure with a planar conjugated core and multiple adsorption sites is obtained. The product molecule contains one 1,3,4-thiadiazole heterocycle, two tertiary amine Mannich structural units, and two thioether bonds, with a molecular weight of 432. It can form multi-point coordination adsorption with the metal surface through heterocycle atoms, thioether bonds, and tertiary amine sites, overcoming the shortcomings of traditional single-Mannich base adsorption, such as low coverage and easy desorption at high temperatures.

[0048] In the preparation of cerium-cysteine ​​chelate, analytical grade cerium chloride heptahydrate and biochemical grade L-cysteine ​​with a purity of over 99% were weighed out at a molar ratio of 1:2.8 and dissolved in deionized water that had been boiled, cooled, and deoxygenated. The reaction vessel was wrapped with aluminum foil throughout the process to prevent light exposure and photodeactivation of cysteine. A 10% sodium hydroxide solution was slowly added at a dropping rate of 1 mL / min to adjust the pH of the system to 5.5. The system temperature was controlled at 38℃, and the chelation reaction was carried out at a constant temperature for 1.5 h under magnetic stirring at 250 r / min. During the reaction, local alkalinity was kept away from the formation of cerium hydroxide precipitate.

[0049] After the reaction was completed, three times the volume of anhydrous ethanol was added to precipitate the solid. After filtration, the filter cake was washed three times with anhydrous ethanol, with the amount of solvent used each time being twice the volume of the filter cake, to wash away unreacted free raw materials. The filter cake was then dried under a vacuum of -0.09 MPa and at 40°C. The material was stirred every 1 hour to prevent local overheating and decomposition. The final chelation rate of the solid chelate was measured to be 92.4%.

[0050] Under weakly acidic conditions, the amino nitrogen atom and mercapto sulfur atom on the L-cysteine ​​molecule act as coordinating atoms, forming three stable five-membered chelate ring structures with trivalent cerium ions. This avoids the hydrolysis of cerium ions in acidic solutions to form hydroxide precipitates. The resulting chelate can be uniformly deposited in the local high pH environment of the metal corrosion cathode area, forming a dense inorganic protective layer that fills the micropores of the organic adsorption membrane. This solves the defects of traditional rare earth salts, such as easy hydrolysis and precipitation, discontinuous film formation, and easy clogging of the reservoir.

[0051] In the preparation of the dispersion stabilizer, two alcohol solvents, ethylene glycol monobutyl ether and isopropanol, were weighed at a mass ratio of 1:1.8. After being mixed evenly, 2% (by mass) of Span80 (based on the total mass of the dispersion stabilizer) was added. The mixture was heated to 35°C at a stirring rate of 200 r / min and stirred at a constant temperature for 15 min until the Span80 was completely dissolved. After natural cooling to room temperature, a homogeneous ternary compound dispersion stabilizer was obtained. Ethylene glycol monobutyl ether improves the solubility of the oil-soluble corrosion inhibitor, isopropanol lowers the freezing point of the system, and Span80 improves the wettability of the metal surface. These three components work synergistically to address the shortcomings of traditional single alcohol solvents, such as poor dispersion and high freezing point of corrosion inhibitors.

[0052] In the corrosion inhibitor preparation process, mechanical stirring with a polytetrafluoroethylene (PTFE) impeller is used throughout to avoid corrosion of metal parts and introduction of impurities. The process is strictly operated according to a three-step procedure: S1. The weighed thiadiazole-modified bis-Mannich base is added to half the amount of deionized water, and the stirring speed is controlled at 300 r / min. The system is heated to 40°C using a water bath at a heating rate of 2°C / min, and stirred at this constant temperature for 15 minutes until the main agent is completely dissolved. During the heating process, excessively rapid heating should be avoided to prevent localized overheating and decomposition of the Mannich base molecules. S2. Maintaining a constant stirring speed and system temperature, the raw materials are added sequentially in the following order: cerium-cysteine ​​chelate, propargyl alcohol polyoxyethylene ether, hexadecyltrimethylammonium bromide, N-allyl thiourea, and potassium iodide. For each component added, stir at a constant temperature for 10 minutes. During stirring, scrape off any adhering material to the stirring paddle and the inner wall of the container. Add the next component only after the current component is completely dispersed and homogeneous to avoid local complexation and agglomeration caused by adding multiple components at the same time. S3. Keep the stirring rate constant and slowly add the dispersant stabilizer over a 5-minute feeding time to avoid excessively high local solvent concentrations that could cause the main agent to precipitate. After adding the stabilizer, continue stirring for 20 minutes. Then add the remaining deionized water to adjust the total mass to 100g and continue stirring at a constant temperature for 30 minutes. Stop stirring when the system is a homogeneous, transparent, reddish-brown liquid. After naturally cooling to room temperature, filter the system through a 100-mesh nylon filter to remove solid impurities and obtain the corrosion inhibitor product.

[0053] The solidification point of the finished product was determined to be -16℃ according to standard methods. Samples were placed in a -20℃ low-temperature constant temperature bath and a 60℃ constant temperature oven, respectively, and sealed for 72 hours. After returning to room temperature, no stratification, crystallization, or precipitation was observed. The transmittance retention rates at 600nm wavelength were 98.2% and 98.7%, respectively. The corrosion inhibitor was added at 1% by mass to a 20% hydrochloric acid solution containing conventional iron ion stabilizers, clay swelling inhibitors, and drainage aids. After standing at 90℃ for 2 hours, the turbidity was 3.2 NTU, with no turbidity or precipitation, indicating good compatibility and meeting the requirements of the well fluid. This solves the defects of existing corrosion inhibitors, such as easy solidification and poor compatibility at low temperatures. This embodiment selects the lower limits of various parameters, resulting in lower addition costs, and is suitable for acidizing operations in shallow to medium-thin non-sulfur-containing reservoirs at 90~120℃.

[0054] Example 2

[0055] Raw material preparation: Based on a total mass of 100g, weigh out 28g of thiadiazole-modified bis-Mannich base, 5g of cerium-cysteine ​​chelate, 4g of propargyl alcohol polyoxyethylene ether, 2.5g of hexadecyltrimethylammonium bromide, 15g of dispersant stabilizer, 2g of N-allyl thiourea, 2g of potassium iodide, with the balance being ultrapure water with a resistivity of 18.2 MΩ·cm. The selected propargyl alcohol polyoxyethylene ether has a degree of polymerization of 5 in its ethylene oxide structural unit, a kinematic viscosity of 20 mm² / s at 25℃, a cloud point of 50℃, and an unreacted propargyl alcohol residue of 0.31%.

[0056] The mass ratio of potassium iodide to hexadecyltrimethylammonium bromide is 1:1.25, which is within the optimal range for synergistic adsorption of anions and cations.

[0057] For each core component, supplementary technical details are provided to ensure full disclosure:

[0058] Thiadiazole-modified bis-Mannich base was used as the core agent. During preparation, 2,5-dimercapto-1,3,4-thiadiazole, paraformaldehyde, and di-n-butylamine were weighed in a molar ratio of 1:2.2:2.1. Anhydrous ethanol, at a mass ratio of 2.5 times the total mass of the raw materials, was added as a solvent. High-purity nitrogen (99.99%) was purged throughout the process to completely isolate oxygen and prevent the oxidation of thiol groups to disulfides, which would reduce adsorption activity. The mixture was stirred and heated to 78°C under constant temperature reflux for 5 hours. Thin-layer chromatography was used to monitor the reaction until the raw material spots completely disappeared, followed by a 30-minute holding period. Vacuum distillation yielded a product with a purity of 98.1%. Mass spectrometry and infrared spectroscopy confirmed that the molecular structure was consistent with the design. The single-molecule adsorption coverage area was more than 1.8 times that of traditional single-Mannich bases, effectively solving the defects of low purity and weak adsorption binding force of traditional Mannich base active components.

[0059] Cerium-cysteine ​​chelate, as a cathodic deposition corrosion inhibitor, was prepared by weighing cerium chloride heptahydrate and L-cysteine ​​in a molar ratio of 1:3.0 and dissolving them in deoxygenated ultrapure water. The entire process was carried out in the dark, with sodium hydroxide solution added dropwise at a constant rate to adjust the pH to 5.8. The system temperature was controlled at 40℃ for 2 hours for constant-temperature chelation reaction. After purification, the chelation rate was measured to be 96.8%. The chelate showed good stability in acid and did not hydrolyze to form cerium hydroxide precipitate. The film deposited on the metal surface was uniform and dense, effectively solving the defects of poor dispersibility and discontinuous film formation of rare earth corrosion inhibitors.

[0060] Propylene alcohol polyoxyethylene ether uses a product with a degree of polymerization of 5, and strictly controls the residual amount of unreacted small molecule propyne alcohol to be less than 0.5%. Compared with traditional small molecule propyne alcohol, it has lower volatility and less toxicity. The alkynyl group on the molecule can form coordination adsorption with the metal surface, and the polyoxyethylene chain can enhance water solubility. It can fill the micropores formed by the adsorption of large-sized organic molecules, effectively solving the defects of traditional small molecule propyne alcohol, such as easy volatility at high temperature, high toxicity, and poor water solubility.

[0061] As a cationic surfactant component, hexadecyltrimethylammonium bromide can be adsorbed onto negatively charged active sites on metal surfaces through electrostatic interactions. The long alkyl chains face the acid to form a hydrophobic barrier. When combined with potassium iodide, it can form an ordered adsorption layer with alternating anions and cations, eliminating the pores in the film caused by the repulsion of like charges in a single cationic surfactant, and effectively solving the defect of poor film density of a single surfactant.

[0062] The dispersant stabilizer adopts a ternary compound system, which is mixed with ethylene glycol monobutyl ether and isopropanol at a mass ratio of 1:2.0. Span80, accounting for 3% of the total mass of the dispersant stabilizer, is added and stirred until completely dissolved. This can not only improve the dispersion stability of each oil-soluble component in water-based acid solutions, but also reduce the overall freezing point of the corrosion inhibitor and improve the wettability of metal surfaces, effectively solving the defects of insufficient dispersion capacity and poor pour point reduction effect of traditional single solvents.

[0063] The molecular formula and reaction principle of the synthesis reaction of thiadiazole modified bis-Mannich base and cerium-cysteine ​​chelate are the same as in Example 1, and the reaction conversion rate and product purity are in the optimal range.

[0064] The preparation of corrosion inhibitors must be carried out strictly according to the three-step method:

[0065] S1. Add thiadiazole-modified bismannich base to half the amount of ultrapure water, heat to 42°C at a rate of 2°C / min while stirring at 300r / min, and stir at a constant temperature for 15min until the main agent is completely dissolved. Observe the state of the system during stirring. When there are no oily droplets or insoluble clumps, it is determined that the dissolution is complete.

[0066] S2. Keep the temperature and stirring rate constant, and add cerium-cysteine ​​chelate, propargyl alcohol polyoxyethylene ether, hexadecyltrimethylammonium bromide, N-allyl thiourea and potassium iodide in sequence. Stir at a constant temperature for 10 minutes after each addition of a component, and scrape off the material adhering to the container wall in time to ensure that all components are evenly dispersed.

[0067] S3. Slowly add the dispersant and stabilizer, stir for 20 minutes, then add the remaining ultrapure water to bring the total mass to 100g. Continue stirring at a constant temperature for 30 minutes, cool to room temperature, and then filter through a 100-mesh nylon filter to obtain the finished product.

[0068] The finished product is a uniform, transparent, reddish-brown liquid with a freezing point of -19℃. After being sealed and stored at -20℃ and 60℃ for 72 hours, the light transmittance retention rates are 99.1% and 99.4%, respectively. When mixed with conventional wellbore additives, the turbidity is 1.8 NTU, with no precipitation or turbidity. All physical and chemical properties meet the requirements for use.

[0069] In this embodiment, the synergistic effect of each component achieves optimal balance, making it suitable for acidizing operations in medium-deep wells and sulfur-containing reservoirs at temperatures of 90~150℃. It solves the shortcomings of existing corrosion inhibitors, such as poor overall performance balance and inability to meet the needs of multiple scenarios.

[0070] Example 3

[0071] Raw material preparation: Based on a total mass of 100g, weigh out 35g of thiadiazole-modified bis-Mannich base, 8g of cerium-cysteine ​​chelate, 6g of propargyl alcohol polyoxyethylene ether, 4g of hexadecyltrimethylammonium bromide, 20g of dispersant stabilizer, 3g of N-allyl thiourea, 4g of potassium iodide, and the balance is deionized water with a resistivity of 15 MΩ·cm. The selected propargyl alcohol polyoxyethylene ether has a degree of polymerization of 6 in its ethylene oxide structural unit, a kinematic viscosity of 25 mm² / s at 25℃, a cloud point of 55℃, and an unreacted propargyl alcohol residue of 0.37%. The mass ratio of potassium iodide to hexadecyltrimethylammonium bromide is 1:1, reaching the upper limit of the synergistic adsorption ratio of anions and cations.

[0072] In the preparation of thiadiazole-modified bis-Mannich base, three reactants were weighed in a molar ratio of 1:2.3:2.2, and anhydrous ethanol (3 times the total mass of the reactants) was added as a solvent. The mixture was refluxed at 80°C for 6 hours under nitrogen protection. Thin-layer chromatography was used to monitor the reaction until complete. The solvent was removed by vacuum distillation to obtain a product with a purity of 96.2%. In the preparation of the cerium-cysteine ​​chelate, cerium chloride heptahydrate and L-cysteine ​​were weighed in a molar ratio of 1:3.2 and dissolved in deoxygenated deionized water. The pH was adjusted to 6.0, and the chelation reaction was carried out at 42°C for 2.5 hours. After purification, the chelation rate was measured to be 93.7%. In the preparation of the dispersion stabilizer, ethylene glycol monobutyl ether and isopropanol were mixed in a mass ratio of 1:2.2, and Span80 (4% of the total mass of the dispersion stabilizer) was added. The mixture was stirred until completely dissolved to obtain a homogeneous dispersion. The molecular formulas and reaction principles of the two core products are the same as in Example 1.

[0073] The corrosion inhibitor preparation process follows a three-step procedure:

[0074] S1. Add thiadiazole-modified bismannich base to half the amount of deionized water, heat to 45°C while stirring at 300 r / min, and stir at a constant temperature for 15 min until the main agent is completely dissolved.

[0075] S2. Keep the parameters constant and add the remaining solid and liquid components in sequence, stirring for 10 minutes after each addition until evenly dispersed.

[0076] S3. Slowly add the dispersant and stabilizer and stir for 20 minutes. Add the remaining deionized water to make up the weight, continue stirring for 30 minutes, and after cooling, filter through a 100-mesh filter to obtain the finished product.

[0077] The finished product has a freezing point of -21℃. After being sealed and stored for 72 hours at -20℃ and 60℃, the light transmittance retention rates are 98.5% and 98.9%, respectively. When mixed with conventional wellbore additives, the turbidity is 2.7 NTU, indicating good compatibility. The dosage of each component in this embodiment represents the upper limit of the formulation, resulting in a thicker corrosion-inhibiting film with stronger high-temperature stability. This makes it suitable for acidizing operations in ultra-deep wells above 150℃ and in high-sulfur reservoirs, addressing the shortcomings of existing corrosion inhibitors in providing insufficient protection under extremely harsh conditions.

[0078] Example 4

[0079] Raw material preparation: The formulation composition is completely consistent with that of Example 2. The only difference is that the cerium-cysteine ​​chelate does not undergo the purification steps of ethanol precipitation, filtration and vacuum drying. After the chelation reaction is completed, the chelation reaction solution is directly added at a purity of 5g of cerium-cysteine ​​chelate. The chelation rate of cerium component in the reaction solution is measured to be 96.2%, and no cerium hydroxide precipitate is produced. The other raw material requirements, the preparation process of thiadiazole modified bis-Mannich base, and the compounding process of dispersion stabilizer are completely the same as those in Example 2.

[0080] The operating parameters for the preparation of the corrosion inhibitor are the same as in Example 2. The stirring, mixing and filtering processes are completed in three steps to obtain the finished product.

[0081] The finished product has a freezing point of -18℃. After being sealed and stored at -20℃ and 60℃ for 72 hours, the light transmittance retention rates were 98.7% and 99.0%, respectively. When mixed with conventional wellbore additives, the turbidity was 2.1 NTU, with no turbidity or precipitation. The suspended solids content was 1.5 mg / L. The compatibility was not significantly different from samples prepared using the purification and addition process. This embodiment eliminates the steps of ethanol precipitation, filtration, and vacuum drying purification of the cerium-cysteine ​​chelate, reducing the consumption of anhydrous ethanol solvent and drying energy during production, thus lowering industrial production costs. It is suitable for batch production needs in large-scale oilfield operations and solves the shortcomings of existing high-performance corrosion inhibitors, such as cumbersome preparation processes and high production costs.

[0082] Comparative Example

[0083] The comparative example used a commonly used acidizing corrosion inhibitor formulation in oilfields. Based on a total mass of 100g, 28g of a traditional acetophenone-formaldehyde-diethylamine monomannich base was weighed. This monomannich base is obtained by reacting acetophenone, a 37% formaldehyde aqueous solution, and diethylamine in a molar ratio of 1:1:1 under reflux at 70℃ for 4 hours. The molecule contains only a single benzene ring and a single tertiary amine adsorption site, resulting in low monomolecular adsorption coverage.

[0084] The remaining components of the formula are 4g of industrial-grade propynyl alcohol, 2.5g of dodecyl dimethyl benzyl ammonium chloride, and 15g of isopropanol, with the balance being deionized water. The preparation process involves adding all raw materials sequentially to a container at room temperature, stirring at 200 rpm for 30 minutes until the system is homogeneous, and then filtering through a 100-mesh nylon filter to obtain the comparative sample.

[0085] The comparative example did not use thiadiazole-modified bis-Mannich base main agent, chelated rare earth components, ternary compound dispersion stabilizers and synergistic corrosion inhibitors. It used isopropanol as a single solvent and directly used small molecule propynyl alcohol as a high-temperature synergistic component. It is completely consistent with the existing mainstream technical solutions described in the background art and is used to conduct parallel performance tests with each example.

[0086] All tests adopted the standard methods commonly used in the oil and gas industry. The metal material used in the tests was N80 casing steel, which is commonly used in oil fields. The average value was taken from three parallel tests, and the relative deviation of the data did not exceed 3% to avoid random errors from interfering with the judgment of the results.

[0087] Table 1 Comparison of static corrosion performance at different temperatures

[0088] Example 1 1.23 3.12 7.89 0.08 Example 2 0.76 1.85 4.32 0.03 Example 3 0.62 1.47 3.56 0.02 Example 4 0.81 1.94 4.57 0.04 Comparative Example 3.68 12.45 26.71 0.32

[0089] Table 1 shows that during the testing process, all steel sheets were subjected to progressive sanding, acetone degreasing, anhydrous ethanol dehydration, drying, and constant weight weighing before testing. After testing, hexamethylenetetramine-hydrochloric acid rust remover was used to remove corrosion products from the steel sheet surface. After rinsing with deionized water, dehydration with anhydrous ethanol, and drying, the steel sheets were weighed at constant weight to calculate the uniform corrosion rate. The maximum depth of pits on the steel sheet surface was measured using a metallographic microscope to calculate the pitting corrosion rate.

[0090] The data in this table shows good stability. The results show that the comparative example, using a traditional single Mannich base combined with propargyl alcohol, provides basic corrosion inhibition at a medium temperature of 90℃. However, the corrosion inhibition film rapidly desorbs at higher temperatures, and the corrosion rate at 150℃ far exceeds the industry standard requirement of ≤10g / (m²•h) for a Class I corrosion inhibitor. Furthermore, the pitting rate is high, easily leading to the risk of localized perforation of the casing. In contrast, the embodiments, through the combination of a multi-adsorption site main agent, chelated rare earth deposition components, and synergistic adsorption aids, achieve corrosion rates meeting the requirements for a Class I corrosion inhibitor across the entire temperature range, with extremely low pitting risk. This effectively solves the shortcomings of traditional corrosion inhibitors, such as insufficient high-temperature protection and high pitting tendency.

[0091] Table 2 Comparison of Storage Stability and Compatibility Performance

[0092] Example 1 -16 98.2 98.7 3.2 2.4 Example 2 -19 99.1 99.4 1.8 1.1 Example 3 -21 98.5 98.9 2.7 1.8 Example 4 -18 98.7 99.0 2.1 1.5 Comparative Example -4 62.3 78.6 18.5 12.7

[0093] Table 2 shows that during the testing process, the freezing point was determined according to the method specified in GB / T510-1983; the transmittance was measured using a UV-Vis spectrophotometer at a wavelength of 600 nm, and the retention rate after storage was calculated based on the transmittance of the freshly prepared sample; the compatibility test involved adding 1% (by mass) of corrosion inhibitor, 1% of complexed iron ion stabilizer, 1% of polycationic clay anti-swelling agent, and 0.5% of fluorocarbon drainage aid to a 20% hydrochloric acid solution, and then measuring the turbidity after standing at 90℃ for 2 hours; the suspended solids content was determined by filtration using a 0.45 μm mixed cellulose membrane.

[0094] The data in this table show good repeatability. The results show that the comparative example, using only isopropanol as a solvent and without stabilization treatment, had a high freezing point, failing to meet the requirements for field operations in environments below -15℃ in winter. After storage at extreme temperatures, the components showed a significant decrease in light transmittance, poor compatibility with other wellbore additives, and a high content of suspended solids in the acid solution, easily clogging reservoir pores. The examples, using ternary compound dispersion stabilizers and chelated rare earth components, exhibit good low-temperature fluidity, excellent stability at extreme temperatures, good compatibility with commonly used wellbore additives, and extremely low suspended solids content, effectively solving the shortcomings of traditional corrosion inhibitors, such as easy freezing and clogging at low temperatures, poor storage stability, and potential reservoir damage.

[0095] Reference Figure 2 This figure visually quantifies the protective performance advantages of the corrosion inhibitor of this invention across different temperature ranges. Traditional single Mannich base combined with propynyl alcohol systems only possess basic corrosion inhibition capabilities at medium and low temperatures. When the temperature rises to 150°C, the adsorbed film rapidly desorbs, and the corrosion rate soars to 26.71 g / (m²•h), far exceeding the industry standard for Class A corrosion inhibitors. The thiadiazole bis-Mannich base of this invention enhances adsorption binding force through multi-point coordination of heterocycles, sulfides, and tertiary amines. Cerium-cysteine ​​chelates are deposited cathodically to fill the pores in the film layer. In the optimal embodiment at 150°C, the corrosion rate is only 3.56 g / (m²•h), meeting the requirements for Class A corrosion inhibitors across the entire temperature range, making it suitable for high-temperature acidizing operations in medium-deep wells.

[0096] Reference Figure 3 This figure compares the low-temperature storage stability and field compatibility of various formulations. Traditional corrosion inhibitors rely on a single isopropanol solvent, resulting in a high freezing point. In winter, they are prone to crystallization and blockage during field storage and transportation. Furthermore, component analysis leads to poor compatibility with well-entry additives such as iron ion stabilizers and clay swelling inhibitors, resulting in high turbidity and suspended solids content, which can easily cause reservoir pore blockage. This invention utilizes a ternary dispersion stabilizer—ethylene glycol monobutyl ether, isopropanol, and Span80—to synergistically reduce pour point and increase solubility. The chelated rare earth components prevent the flocculation of free metal ions. The freezing point is as low as -21°C, and the light transmittance retention rate is over 98% even at extreme temperatures. The compatibility turbidity is below 3.2 NTU, meeting the requirements for all-season oilfield field operations.

[0097] Reference Figure 4This radar chart comprehensively evaluates product performance from multiple dimensions, including corrosion inhibition efficiency, pitting corrosion resistance, storage and transportation stability, and compatibility. Traditional Mannich base corrosion inhibitors suffer from multiple shortcomings, such as insufficient high-temperature protection, easy solidification at low temperatures, and poor compatibility, making them difficult to adapt to complex downhole conditions. This invention achieves comprehensive improvements in high-temperature corrosion inhibition, pitting corrosion resistance, all-temperature storage, and on-site compatibility through the synergistic effects of a multi-adsorption-site organic main agent, a chelated rare earth cathode deposition film, an ordered anion and cation adsorption layer, and a ternary dispersion stabilization system. All indicators meet the standards of a Class I corrosion inhibitor, covering diverse acidizing operation needs from shallow to ultra-deep wells and from conventional to sulfur-containing reservoirs.

[0098] Reference Figure 5 The line graph clearly reflects the impact of temperature increase on the protective performance of the two types of corrosion inhibitors. Traditional corrosion inhibitors exhibit an exponential increase in corrosion rate with rising temperature, severely exceeding the limit above 120℃, and showing significant film desorption failure characteristics at high temperatures. In contrast, the corrosion rates in Examples 2 and 3 of this invention rise gradually with temperature, remaining below 5 g / (m²•h) even at 150℃. This indicates that the synergistic film layer of multi-point chemical adsorption of thiadiazole bis-Mannich base and cerium chelate deposition passivation possesses excellent thermal stability and anti-desorption ability, providing reliable protection continuously over a wide temperature range and solving the industry-wide common problem of rapid high-temperature failure of conventional corrosion inhibitors.

[0099] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A composite oilfield acidizing corrosion inhibitor, characterized in that, By mass fraction, the raw material composition includes: 20-35 parts of thiadiazole modified bismannich base, 3-8 parts of cerium-cysteine ​​chelate, 2-6 parts of propargyl alcohol polyoxyethylene ether, 1-4 parts of hexadecyltrimethylammonium bromide, 10-20 parts of dispersant stabilizer, and the balance being deionized water. The thiadiazole-modified bismannich base is prepared by dissolving 2,5-dimercapto-1,3,4-thiadiazole, paraformaldehyde, and di-n-butylamine in anhydrous ethanol at a molar ratio of 1:2.1~2.3:2.0~2.2, reacting under constant temperature reflux at 75~80℃ for 4~6 hours, and then removing the solvent by vacuum distillation to obtain the product. The cerium-cysteine ​​chelate is obtained by dissolving cerium chloride heptahydrate and L-cysteine ​​in deionized water at a molar ratio of 1:2.8~3.2, adjusting the pH of the system to 5.5~6.0, and chelating at a constant temperature of 38~42℃ for 1.5~2.5h.

2. The composite oilfield acidizing corrosion inhibitor according to claim 1, characterized in that, The composition of each raw material by mass parts is as follows: 28 parts of thiadiazole modified bismannich base, 5 parts of cerium-cysteine ​​chelate, 4 parts of propargyl alcohol polyoxyethylene ether, 2.5 parts of hexadecyltrimethylammonium bromide, 15 parts of dispersant stabilizer, and deionized water to make up to a total mass of 100 parts.

3. The composite oilfield acidizing corrosion inhibitor according to claim 1, characterized in that, The degree of polymerization of the oxyethylene structural unit of the propargyl alcohol polyoxyethylene ether is 4~6, the kinematic viscosity is 15~25mm² / s at 25℃, and the cloud point is 45~55℃.

4. The composite oilfield acidizing corrosion inhibitor according to claim 1, characterized in that, In the preparation of the cerium-cysteine ​​chelate, the pH value of the system is adjusted by a 10% sodium hydroxide dilute solution. After the reaction is completed, three times the volume of anhydrous ethanol is added to the system to precipitate the solid product. After filtration and vacuum drying at 40°C, the chelation rate of the solid chelate is not less than 92%.

5. The composite oilfield acidizing corrosion inhibitor according to claim 1, characterized in that, The dispersion stabilizer is composed of ethylene glycol monobutyl ether, isopropanol and Span80, wherein the mass ratio of ethylene glycol monobutyl ether to isopropanol is 1:1.8~2.2, and the amount of Span80 added accounts for 2%~4% of the total mass of the dispersion stabilizer.

6. The composite oilfield acidizing corrosion inhibitor according to claim 1, characterized in that, The raw material composition also includes 1 to 3 parts of N-allyl thiourea, wherein the purity of N-allyl thiourea is not less than 98%.

7. The composite oilfield acidizing corrosion inhibitor according to claim 6, characterized in that, The raw material composition also includes 0.5 to 2 parts of potassium iodide, and the mass ratio of potassium iodide to hexadecyltrimethylammonium bromide is 1:1 to 1.

5.

8. The composite oilfield acidizing corrosion inhibitor according to claim 1, characterized in that, The molecular structure of the thiadiazole-modified bisMannich base includes a 1,3,4-thiadiazole heterocycle, two tertiary amine Mannich structural units, and two thioether bonds. It can form multi-point coordination adsorption with the carbon steel surface through the sulfur atoms, nitrogen atoms, thioether bond sulfur atoms, and tertiary amine nitrogen atoms on the heterocycle. The molecular weight of the product is 432.

9. The composite oilfield acidizing corrosion inhibitor according to claim 1, characterized in that, The corrosion inhibitor is a uniform, transparent, reddish-brown liquid with a freezing point below -15℃. It does not separate, crystallize, or precipitate after being stored for 72 hours in a temperature range of -20℃ to 60℃. It does not produce turbidity or precipitation when mixed with commonly used iron ion stabilizers, clay swelling inhibitors, and drainage aids in oil fields, and has good compatibility.

10. A method for preparing a composite oilfield acidizing corrosion inhibitor, used to prepare the composite oilfield acidizing corrosion inhibitor according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Weigh the thiadiazole-modified bismannich base according to the formula amount, add it to half of the formula amount of deionized water, heat it to 40~45℃ at a stirring rate of 300r / min, and stir at a constant temperature for 15min until the main agent is completely dissolved. S2. Keep the stirring rate and temperature constant, and add the formulated amounts of cerium-cysteine ​​chelate, propargyl alcohol polyoxyethylene ether, and hexadecyltrimethylammonium bromide to the system in sequence. After each addition of a component, stir at a constant temperature for 10 minutes until the system is completely homogeneous. S3. Keep the stirring rate constant, add the amount of dispersant and stabilizer specified in the formula to the system, stir for 20 minutes, then add the remaining deionized water, continue stirring for 30 minutes until the system is uniform and transparent, cool naturally to room temperature, and then filter through a 100-mesh filter to obtain the finished composite oilfield acidizing corrosion inhibitor.